Effect Of Demonetization And Its Impact On Students Staying Away From Home ((PJHAS) PUSA Journal of Hospitality and Applied Sciences, 2017)
Background: Corruption is a big issue in our country which needs to be tackled. Demonetization  was a step taken by government to control corruption but it had an adverse effect on the students.  Delhi being the pioneer hub of educational institutions, students from different parts of the country  and worldwide stay away from home for education. Being self dependent and away from their  families, students are mostly dependents on the ATMs and banks. Objectives: To analyze the impact  of demonetization on students staying away from home. Methodology: The study was conducted  among 240 students of IHM, Pusa. Subjects (n=240) were selected through random sampling  comprising of both male and female in age group of 17-25 years and staying in both PG’s and  Hostels. A questionnaire was designed to collect the data regarding their experience during the  period of more than one and a half month of demonetization. Results: The findings of this research  revealed that students suffered from financial crisis for about 30 days due to limited number of ATMs  with cash in the vicinity and banks were unable to provide with the cash to meet the needs. 79%  students accepted that they faced difficulties during demonetization. Conclusion: Demonetization  not only affected the students financially but also resulted in mental and physical stress. However  the results shows a positive sign and that students supported this step as a tool against corruption.
Keywords: Demonetization; Notes; Bills; Inflation; Currency; E-Transactions; E-Wallet; Cash Crunch